Exploiting macrocyclic polylactam for sensing V-series nerve agents: A computational study - Dipankar Das; Bishwajit Ganguly (Results in Chemistry, 2024)
The nerve agents are organophosphorus compounds (OPs) developed as chemical warfare agents (CWAs) that inhibit acetylcholinesterase (AChE) and lead to impeding neurological signals in mammals. Therefore, detecting such nerve agents is important, and efforts to study the fundamental interactions of host systems with CWAs are scarce in the literature. In this report, the cyclic 18-membered tetralactam [Ⅰ] as a host molecule has been chosen to sense V-series nerve agents. The DFT calculated results reveal that VM, VG, and VX, bind strongly with the core unit of the host molecule tetralactam [Ⅰ] with a preference for VM. The remarkably higher binding affinity of VM is governed by more hydrogen bonding interactions with the core of the cyclic 18-membered tetralactam [Ⅰ]. The nerve agent Russian VX has been found to bind weakly with the receptor molecule. The hydrogen bonding interactions of these nerve agents have further been analyzed with non-covalent interactions (NCI) and atoms in molecule (AIM) calculations. The tetralactam moiety exhibits the binding with V-series nerve agents and the absorption spectral results can be used as diagnostic signatures for sensing of such nerve agents in useful applications.